2021
DOI: 10.1093/ejo/cjab070
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion severity and its associations with oral health-related quality of life in an adult population

Abstract: Summary Aim The aim of this study was to investigate malocclusion severity and its associations with oral health-related quality of life (OHRQoL) among middle-aged adults. Materials and methods The study material consisted of 1786 subjects from the Northern Finland Birth Cohort 1966 who attended dental and oral examination as part of the 46-year-old follow-up study. Malocclusion severity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…In line with this, the Finnish researchers Närhi et al [24], observed from a prospective study, which aimed to investigate the different levels of malocclusion and their associations with quality of life related to oral health in 1786 middle-aged adults who, in addition to the high prevalence of dentofacial alterations, there was a directly proportional association between the severity of malocclusions and quality of life related to oral health, and that women are the most affected ones by this worsening quality of life.…”
Section: Discussionmentioning
confidence: 69%
“…In line with this, the Finnish researchers Närhi et al [24], observed from a prospective study, which aimed to investigate the different levels of malocclusion and their associations with quality of life related to oral health in 1786 middle-aged adults who, in addition to the high prevalence of dentofacial alterations, there was a directly proportional association between the severity of malocclusions and quality of life related to oral health, and that women are the most affected ones by this worsening quality of life.…”
Section: Discussionmentioning
confidence: 69%
“…The malocclusions that have the greatest impact on the OHRQoL of patients are anterior crossbite, dental crowding, and Class III malocclusion [ 36 ]. In the scientific literature, there are few articles that analyze the impact of having an anterior open bite on OHRQoL in adult patients, with most evaluating child and/or adolescent patients [ 15 , 16 , 17 , 20 , 21 , 22 ]. This can be explained, in part, by the fact that, today, the majority of orthodontic patients are children; however, increasingly more adult patients are requesting orthodontic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have evaluated the impact of other malocclusions on the oral quality of life of patients [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 35 , 38 ]. Masood M et al in 2014 evaluated the impact of having a posterior crossbite on OHRQoL in young patients (143 patients aged 15–25 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dog, forskningslitteraturen er ikke entydig på den langsiktige nytten av kjeveortopedisk behandling (15). I forbindelse med bittavvik og livskvalitet er det bare dokumentert en svak, inkonsistent relasjon mellom alvorligheten av bittavvik og effekten på livskvalitet (16). Det noen anser for å vaere et kosmetisk bittavvik, kan for andre vaere av stor betydning for livskvalitet.…”
Section: Psykososiale Effekter Av Bittavvikunclassified